Science and innovation policy for the new knowledge economy - Colombo, Massimo G. (Edward Elgar Publishing Ltd. CheltenhamGB, 2011)
Provides a critical examination of the state of the art of some important STI policy research fields. Focuses on specific areas of intervention, both analysing and evaluating the effectiveness of implemented policy measures in these areas.